Reading networks in children with dyslexia compared to children with ocular motility disturbances revealed by fMRI - Saralegui, Ibone; Ontañón, José M.; Fernandez-Ruanova, Begoña; Garcia-Zapirain, Begonya; Basterra, Alejandro; Sanz-Arigita, Ernesto J. (Frontiers in Human Neuroscience, 2014)
Developmental dyslexia is a neurological disorder whose underlying biological and cognitive causes are still being investigated, a key point of great significance, because it will determine the best therapeutic approach to use. Using functional magnetic resonance imaging, we studied the brain activation pattern while reading in the most eloquent cortical areas from the two reading routes, phonological and orthographic, and the strength of their association with reading scores in 66 Spanish children aged 9-12 years divided into three groups: typically developing readers (controls), dyslexic readers and readers with monocular vision due to ocular motility disorders but with a normal reading development, to assess whether (or not) the neuronal network for reading in children with dyslexia has similarities with that in children with impaired binocular vision due to ocular motility disorders. We found that Spanish-speaking children with dyslexia have a brain circuit for reading that differs from that in children with monocular vision. Individuals with dyslexia tend to hypoactivate some of the more eloquent areas in the left hemisphere engaged by the phonological route, especially the visual word form area and left Wernicke´s area, and try to compensate this deficit by activating eloquent areas related to the orthographic route, such as the anterior part of the visual word form area and the posterior regions of both middle temporal gyri. That is, they seem to compensate for impairment in the phonological route through orthographic routes of both hemispheres. Our results suggest that ocular motility disturbances do not play a causal role in dyslexia. Dyslexia seems to be a neurological disorder that requires early recognition and evidence-based assessments and treatment to achieve the best possible outcome.